A Phenomenological Study on the Dynamics of Work-Family Balance in Dual-career Mothers toward Family Well-being - Susilowati, Hadina Pramesti Diba; Nurhayati, Siti Rohmah (Journal of Family Sciences, 2025)
Role balance is essential for dual-career mothers to perform optimally in both work and family domains.  The purpose of this study was to understand how dual-career mothers with children achieved work–family balance to promote family well-being. This study used a qualitative approach employing a phenomenological research design. The sample for this study was selected through purposive technique consisting of four mothers who have dual-careers, children, and are not in a long-distance relationship with their husbands. The data analysis technique used is interpretative phenomenological analysis (IPA). The results indicated that there were five components that supported work–family balance among dual-career mothers, namely dual role balance, work–family balance motivation, family support, dual-career impact, and family well-being. A positive and supportive family environment played a major role in contributing to mothers’ success in achieving a balance between work and family. This study contributes to a better understanding of how dual-career mothers can manage role demands, with potential implications for enhancing family functioning and well-being.